Role of EGF on in situ culture of equine preantral follicles and metabolomics profile. (December 2017) - Aguiar, F.L.N.; Lunardi, F.O.; Lima, L.F.; Bruno, J.B.; Alves, B.G.; Magalhães-Padilha, D.M.; Cibin, F.W.S.; Berioni, L.; Apgar, G.A.; Lo Turco, E.G.; Gastal, E.L.; Figueiredo, J.R.
Abstract: The effects of epidermal growth factor (EGF) concentrations (0, 10, 50, and 100 ng/ml) on in vitro culture (IVC) of equine preantral follicles were evaluated using histology, estradiol and reactive oxygen species (ROS) production and metabolomics. After IVC, the percentage of normal follicles was lower ( P < 0.05) for all treatments when compared to non-cultured control. EGF 50 ng/ml treatment had more ( P < 0.05) normal follicles at Day 7 of culture when compared with EGF 0 and 100 ng/ml. EGF 50 ng/ml had more ( P < 0.05) developing follicles than the 0 ng/ml and 10 ng/ml EGF treatments. Follicular and oocyte diameters were greater ( P < 0.05) with EGF 50 ng/ml than the other cultured treatments, but similar ( P > 0.05) to the non-cultured control. From Day 1 to Day 7 estradiol production increased ( P < 0.05) in all EGF treatments. EGF 50 ng/ml was the only treatment that maintained ROS production through IVC. Metabolomics profiles of the spent media indicated that eleven ions from variable influence in the projection (VIP) scores were higher represented in the EGF 50 ng/ml treatment. In conclusion, EGF 50 ng/ml treatment maintained follicle survival and ROS production, and promoted activation of cultured equine preantral follicles enclosed in ovarian tissue. Highlights: Effects of EGF on in vitro culture of equine preantral follicles EGF 50 ng/ml treatment was beneficial for follicular morphology and development. Estradiol production increased in all EGF treatments from Day 1 to Day 7 of culture. EGF 50 ng/ml was the only treatment that maintained ROS production. Metabolomics profile indicated highly represented ions in EGF 50 ng/ml treatment.